Circulating galectin-3 promotes tumor-endothelium-adhesion by upregulating ICAM-1 in endothelium-derived extracellular vesicles - Wang, Lei; Du, Dan-Dan; Zheng, Zong-Xue; Shang, Peng-Fei; Yang, Xiao-Xia; Sun, Chao; Wang, Xiao-Yan; Tang, Ya-Jie; Guo, Xiu-Li (Frontiers in Pharmacology, 2022)
Graphical Abstract